2015
DOI: 10.1080/14786419.2015.1043553
|View full text |Cite
|
Sign up to set email alerts
|

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity

Abstract: A new cytotoxic dimeric naphthopyrone, aurasperone H (1), together with eight related known polyketides (2-9) was isolated from a marine-derived fungus Aspergillus niger 2HL-M-8. The structure of new compound 1 was elucidated on the basis of its spectroscopic data (1D, 2D NMR and CD). Compound 1 exhibited moderate inhibitory activity against the human lung adenocarcinoma A549 and the human leukaemia HL-60 cell lines. Compound 5 displayed significant in vitro antiproliferative activity against HL-60 cell line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Recently, a growing number of Aspergillus spp. fungi, have been reported to produce novel bioactive compounds, such as butenolide derivatives as anti-inflammatory agents (Liu et al 2018), aurasperone H as anticancer (Li et al 2016), asperchondols A and B as antibacterials (Liu et al 2017), aspergivones A and B with anticancer and antibacterial activities (Ma et al 2017b), and aspochalasin B and D as antibacterials (Ratnaweera et al 2016). In this section, we discuss bioactive metabolites of Aspergillus spp., isolated from terrestrial environments, that shown antibacterial activities and could provide further cues for clinical trials.…”
Section: Antibacterial Metabolites From Terrestrial Aspergillus Sppmentioning
confidence: 99%
“…Recently, a growing number of Aspergillus spp. fungi, have been reported to produce novel bioactive compounds, such as butenolide derivatives as anti-inflammatory agents (Liu et al 2018), aurasperone H as anticancer (Li et al 2016), asperchondols A and B as antibacterials (Liu et al 2017), aspergivones A and B with anticancer and antibacterial activities (Ma et al 2017b), and aspochalasin B and D as antibacterials (Ratnaweera et al 2016). In this section, we discuss bioactive metabolites of Aspergillus spp., isolated from terrestrial environments, that shown antibacterial activities and could provide further cues for clinical trials.…”
Section: Antibacterial Metabolites From Terrestrial Aspergillus Sppmentioning
confidence: 99%
“…Naphthopyrones are well-known to possess nonselective activities in biological systems and exhibit antimicrobial [28], cytotoxic [29], antimycobacterial [30], and antimalarial [31] independently from their antimicrobial activity. Conclusively, even though the mode of action of the pigmentosins remains to be studied, they constitute promising candidates for combination therapy with existing or novel antibiotics.…”
Section: Bioactivitiesmentioning
confidence: 99%
“…By comparing the spectroscopic data (HRESIMS, 1 H and 13 C NMR, Figures S9–S60) with those reported in the literature, the remaining nineteen known compounds ( 2 – 21 ) were identified as 2-benzyl-4 H -pyran-4-one ( 2 ) [11], asperpyrone D ( 3 ) [12], asperpyrone C ( 4 ) [13], aurosperone B ( 5 ) [14], fonsecinone B ( 6 ) [14], asperpyrone B ( 7 ) [15], dianhydro-aurasperone C ( 8 ) [12], isoaurasperone A ( 9 ) [15], aurasperone F ( 10 ) [16], fonsecinone D ( 11 ) [14], asperpyrone A ( 12 ) [12], fonsecinone A ( 13 ) [15], fonsecin ( 14 ) [14], TMC 256 A1 ( 15 ) [17], flavasperone ( 16 ) [14], carbonarone A ( 17 ) [18], pestalamide A ( 18 ) [19]. In addition, the p configuration of 12 was defined by ECD calculation at the B3LYP/6-311+G(d, p) level (Figure 2, Supplementary Materials, S34–S36).…”
Section: Resultsmentioning
confidence: 99%
“…Natural naphthopyrones have been previously reported for their anticancer potential [13,15,17]. Therefore, the present study evaluated the inhibitory effects of the isolated compounds on five human cancer cell lines (PANC-1, A549, MDA-MB-231, Caco-2, and SK-OV-3), and one human normal cell line (HL-7702) at a concentration of 50 µM.…”
Section: Resultsmentioning
confidence: 99%